Rhizobium biology and biotechnology - Hansen, Alexander P. (Springer, 2017)
This book provides a valuable contribution to the field of agriculture microbiology and pooled research in the form of a compendium describing the benign functional role of Rhizobium spp., with biotechnological perspectives on maintaining agroecosystem sustainability. Topics include the occurrence and distribution of Rhizobium; the phenotypic and molecular characteristics of Rhizobium; the impact of Rhizobium on other microbial communities in the rhizosphere; the N2-fixation ability of Rhizobium; Rhizobium and abiotic/biotic stress; Rhizobium-mediated restoration of an ecosystem; and in silico analysis of rhizobia pool, and Biotechnological perspectives of Rhizobium.
Includes index.
Keywords: Rhizobium.; elektronické knihy; electronic books